Diversity of Fiddler Crab (Uca spp.) in The Mangrove Area of Gerupuk Beach Central Lombok - Susanti, Yeni; Jufri, Abdul Wahab; Syukur, Abdul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The great influence that ball crabs have on changes in the physical and biochemical aspects of the environment so that they become biota that inhabit microhabitats. Mangrove ecosystem, this can have an impact on the quantity and diversity of fiddler crab species (Uca spp.). One of the coastal locations of Central Lombok is quite large, namely Gerupuk Beach. The purpose of this study was to diversity of fiddler crabs and distribution pattern in the mangrove area of Gerupuk Beach, Central Lombok and to see the validity of the learning videos in this study. The quadratic transect approach was used to conduct the field study from December 2024 to February 2025. Convenience was used to decide the research stations. There were 247 fiddler crabs (Uca spp.) in all stations, according to the results. These individuals were divided into four subgenus and included seven different species: Uca perplexa, Uca triangularis, Uca tetragonon, Uca crassipes, Uca bellator, Uca dussumeiri, and Uca forcipata. The three stations' diversity (H'), which was classified as medium level, ranged from 1.318 to 1.897. The evenness index (E) ranged from 0.677 to 0.975, falling within the relatively even range. Additionally, fiddler crabs' dominance index (C) falls between 0.156-0.310 for the low dominance category.